2018
DOI: 10.2196/mhealth.8304
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Apps for Mindfulness Interventions for Suicidality in Asian Youths: Literature Review

Abstract: BackgroundThe advent of mobile technology has ushered in an era in which smartphone apps can be used as interventions for suicidality.ObjectiveWe aimed to review recent research that is relevant to smartphone apps that can be used for mindfulness interventions for suicidality in Asian youths.MethodsThe inclusion criteria for this review were: papers published in peer-reviewed journals from 2007 to 2017 with usage of search terms (namely “smartphone application” and “mindfulness”) and screened by an experienced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Clinical psychology educators in Singapore could use the preliminary qualitative findings from this study to enhance their understanding of trainees’ perspectives, for consideration when designing their teaching methodologies to cater to a range of learning styles. In view of the advent of mobile technology in our contemporary society [1,2,3,4], the inclusion of m-learning has the potential to tap upon the advantages of the mobile platform [5]. Our preliminary findings serve to encourage educators to collaborate with researchers to further innovative research in the area, and continue to gather evidence to support a contemporary step beyond the traditional classroom, in our innovation to enhance flexible and continuous learning that is not confined to the physical traditional classroom space [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical psychology educators in Singapore could use the preliminary qualitative findings from this study to enhance their understanding of trainees’ perspectives, for consideration when designing their teaching methodologies to cater to a range of learning styles. In view of the advent of mobile technology in our contemporary society [1,2,3,4], the inclusion of m-learning has the potential to tap upon the advantages of the mobile platform [5]. Our preliminary findings serve to encourage educators to collaborate with researchers to further innovative research in the area, and continue to gather evidence to support a contemporary step beyond the traditional classroom, in our innovation to enhance flexible and continuous learning that is not confined to the physical traditional classroom space [6].…”
Section: Discussionmentioning
confidence: 99%
“…With the rising trend in e-technology [1,2], the advancement of smartphones has ushered in an era where smartphone applications can be used to enhance teaching and learning [3,4]. M-learning is often referred to as the learning that takes advantage of mobile technologies, to occur without being limited to a fixed place [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature highlighted the importance of interventions delivered using smartphone apps, in view of the potential to reduce health care costs in Asia [37]. In comparison to Western countries, there is a shortage of mental health professionals in Asia, yet a high penetration of mobile phone usage throughout Asia, with Singapore alone reporting that smartphone adoption rates far exceeded the population.…”
Section: Discussionmentioning
confidence: 99%
“…An efficient way to curtail this difficulty will be to conduct attentional bias re-training over mobile devices, given their benefits for high-dosage treatment delivery, and prevalent usage and convenience. Additionally, it was suggested that electronic interventions delivered via mobile phone apps could enhance patient-centered care in an increasingly technology-savvy society, underscoring the importance of interventions delivered using electronic platforms [36,37,38]. Smartphone apps have been used to deliver psychological therapies such as addiction treatment [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation